Relação morfométrica e de competição no crescimento de Ocotea porosa (Nees et Martius ex Nees) Liberato Barroso na região central de Santa Catarina - Weber, Veridiana Padoin (2013)
The canopy of trees is most directly responsible for the growth, being influenced by the type of management adopted in afforestation and competition between individuals. Thus, the aim of this study was to describe the morphology and growth of relations Ocotea porosa using mathematical modeling and considering the effect of competition. Data collection was conducted in EMBRAPA / EPAGRI Forest Reserve in Caçador (SC) and the native forest in Laminados AB Company located in Calmon (SC). The Diameter at Breast Height (DBH) dimensions have been found in the sample from 10 cm to 80 cm, whereas random sampling and circular plots of variable area, and the radius of each plot the distance between the tree and the competitor farthest point sampling (central tree). Calculated variables describing the size and competition were the Diameter at Breast Height in shell Diameter at Breast Height shelled, basal area, crown diameter, canopy area, the potential number of trees per hectare, comprehensiveness index, index overhang, formal canopy, the h / d, percentage of canopy index BAL (Basal Area Larger), Hegyi index, indexes Glover and Hool, indexes Tomé and Burkhart, Lorimer index and index of Clark and Evans. The variables whose explained better of the regular annual percentage increase in basal area were diameter at breast height and vitality Cup, being also considered significant in the model the salience index and the BAL competition index. The best model for hypsometric relation was that of Chapman Richards (h = 20,6053.(1 e-0,0615.dbh), taking as an alternative to model of Stofells (ln(h) = 1,68412 + 0,32665.ln(dbh)) and to estimate the canopy diameter was the logarithmic (ln(dc) = -1,76773 + 11,05485.ln(dbh), for symmetric tops, and ln(dc) = -1,19837 + 0,88682.ln(dbh), to represent the asymmetric tops). The estimate of crown diameter to the Diameter at Breast Height will be used separately for locations where there is greater competition from places where there is less competition due to different symmetry as a consequence of this variable.